Efektivitas Penerimaan Santri Baru Melalui Sosial Media - Muhammad Rizaldi Pratama (Jurnal Riset Komunikasi Penyiaran Islam, 2022)
Abstract. The phenomenon of social media presence as a result of the extraordinary development of information and communication technology. With a variety of services that can be used, social media can change the way we communicate. The Baitul Hidayah Islamic Boarding School is one of the schools that aims to share information and try to use social media as a communication tool in spreading its activities. Through the research conducted by the author on the effectiveness of attracting new students through social media, the background to the problem was found as follows: What publications were implemented in The Baitul Hidayah Islamic boarding school in the recruitment of new students. The purpose of this study is to know the publications that are made at The Baitul Hidayah Islamic Boarding School in the recruitment of new students. To find out how the process of admission of new students to the Baitul Hidayah Islamic Boarding School is carried out. To find out the effectiveness of disseminating students’ activities in the Baitul Hidayah Islamic School through social media. The research method used is the quantitative method with uses and effects theory and it uses data collection techniques through questionnaires, documentation and interviews. The data analysis technique used is validation test, reliability test and normality test. The research method used is the quantitative method with uses and effects theory and it uses data collection techniques through questionnaires, documentation and interviews. The data analysis technique used is validation test, reliability test and normality test. The results of the research show that the student activities dissemination program for recruiting new students is very effective, and the student activities dissemination shows that obtained based on the outputs of the analysis, and the data derived from the research results indicate that the dissemination of student activities has an impact on the employment of new students. Abstrak. Fenomena kehadiran media sosial sebagai perkembangan informasi dan teknologi komunikasi sangat luar biasa. Dengan berbagai layanan yang dapat digunakan, media sosial dapat mengubah cara kita berkomunikasi. Pondok Pesantren Baitul Hidayah adalah salah satu pesantren yang bertujuan untuk berbagi informasi menggunakan media sosial sebagai alat berkomunikasi dalam mensosialisasikan kegiatan-kegiatannya. Penelitian yang penulis lakukan mengenai Efektivitas penerimaan santri baru melalui sosial media, adapun penelitian bertujuan mengetahui publikasi apa saja yang dilakukan di Pondok Pesantren Baitul Hidayah dalam penerimaan santri baru. Untuk mengetahui bagaimana proses mekanisme penerimaan santri baru di Pondok Pesantren Baitul Hidayah. Untuk mengetahui efektivitas publikasi kegiatan santri di Pondok Pesantren Baitul Hidayah melalui media sosial. Metode penelitian yang digunakan adalah metode kuantitatif dengan teori uses and effects dengan menggunakan teknik pengumpulan data melalui kuisioner, dokumentasi, dan wawancara. Teknik analisa data yang digunakan adalah uji validasi, uji reliabilitas, dan uji normalitas. Hasil penelitian menunjukan bahwa program publikasi kegiatan santri terhadap recruitment santri baru cukup efektif, publikasi kegiatan santri menggambarkan bahwa diperoleh berdasarkan output analisisnya, data dari hasil penelitian yang menunjukkan bahwa publikasi kegiatan santri memberi pengaruh terhadap penerimaan santri baru.